1972
DOI: 10.1126/science.177.4055.1205
|View full text |Cite
|
Sign up to set email alerts
|

Human Prolactin: 24-Hour Pattern with Increased Release during Sleep

Abstract: Human prolactin was measured in plasma by radioimmunoassay at 20 minute intervals for a 24-hour period in each of six normal adults, whose sleep-wake cycles were monitored polygraphically. A marked diurnal variation in plasma concentrations was demonstrated, with highest values during sleep; periods of episodic release occurred throughout the 24 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
119
1
5

Year Published

1974
1974
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(148 citation statements)
references
References 12 publications
(3 reference statements)
23
119
1
5
Order By: Relevance
“…In this case, a direct correlation between physical contact and prolactin levels may not be possible since the daily first-morning urine sample measures accumulated prolactin rather than the immediate changes that occur in the blood while caretakers carry the newborns, as shown by Dixson and George (1982) and Roberts et al (2001) and the present study. Furthermore, the metabolic clearance rate and half-life of plasma prolactin in nonhuman primates are poorly understood, but, in humans, its increase lasts around 50 min (Sassin et al, 1972;Sievertsen et al, 1980), supporting the association between the plasma prolactin levels and physical contact during carrying found here.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this case, a direct correlation between physical contact and prolactin levels may not be possible since the daily first-morning urine sample measures accumulated prolactin rather than the immediate changes that occur in the blood while caretakers carry the newborns, as shown by Dixson and George (1982) and Roberts et al (2001) and the present study. Furthermore, the metabolic clearance rate and half-life of plasma prolactin in nonhuman primates are poorly understood, but, in humans, its increase lasts around 50 min (Sassin et al, 1972;Sievertsen et al, 1980), supporting the association between the plasma prolactin levels and physical contact during carrying found here.…”
Section: Discussionsupporting
confidence: 81%
“…A 50-min time lapse was observed prior to data collection and between two successive episodes of carrying to prevent a possible cumulative effect of the preceding carrying episode/physical contact on prolactin levels and because little is known about the metabolic clearance rate and half-life of this hormone in the plasma of nonhuman primates. For humans, it has been demonstrated that the prolactin increase lasts around 50 min (Sassin et al, 1972;Sievertsen et al, 1980). Blood sample collection was made either interrupting the carrying bout or waiting for the bout to end and removing the focal animal and the newborns from their cage.…”
Section: Behavioral Measurementioning
confidence: 99%
“…The same study also found a greater GH release in male than in female rats; the synthesis of GH was little affected by age in females. In adult human males and females, however, another study involving the measurement of PRL secretion over a 24-h period did not find a gender difference (Sassin et al, 1972).…”
Section: Discussionmentioning
confidence: 86%
“…As prolactin levels have been reported to be constant between 10 a.m. and 5 p.m. (Sassin et al 1972), the higher levels on day 2 than on day 3 cannot be ascribed to circadian variation. The decreasing prolactin levels with increasing duration on AMPT may be due to the fact that the rise in prolactin may be related to the rate of DA depletion rather than to a constant amount of DA depletion, and that with more constant DA depletion internal feedback circuits are increasingly able to mitigate the effect of DA depletion on prolactin levels.…”
Section: Plasma Prolactinmentioning
confidence: 85%